PENERAPAN PENDEKATAN RECIPROCAL TEACHING TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR MATEMATIS SISWA SMP - Dewi Nuraeni; Inri Rahmawati; Zuli Nuraeni (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2016)
Dewi Nuraeni (NIM 123223005), Aplication of Reciprocal Teaching learning Critical Thinking Skills of mathematical Student SMP, Mathematics Education Program, 2016, 366 pages. This study aims to determine (1) what critical thinking skills that derive mathematical study of mathematics by reciprocal teaching-learning approach is better than students who received conventional learning, (2) what there is an increase in critical thinking skills in students who obtain a mathematical study of mathematics by teaching reciprocal learning approach, (3) how the students response reciprocal-teaching learning approach to improving the critical thingking ability of students mathematical. The research method that used in this study is quasi eksperimental method by using the design research non equivalent control group design. The population in this study is eighth grade student of SMPN 1 Lebakwangi 2015/2016. By using the method of purposive sampling, obtained two samples of the VIII-A as experimental class and VIII-B as sample class. The instrument used to determine the mathematics learning achievment is a form of assay test, while to know the students' responses to learning using reciprocal teaching approach used questionnaire